Teknologi Augmented Reality Sebagai Media Pembelajaran Dalam Pengenalan Buah-Buahan (Kasus Paud Hidayatul Burhan) - Maelani, Yeyen; Irawan, Agung Susilo Yuda; Suharso, Aries (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Paud Hidayatul Burhan is an Early Childhood Education which is located in Pasirtanjung Village, Lemahabang District, Karawang Regency. Currently, teachers are demanded to be creative in providing education to their students with various methods such as the rationalization of plant themes for fruits and so on. Due to the lack of educational facilities for this use of media, it is necessary to use technology to attract children's interest and motivation to learn. In this case, the fruit learning media still uses conventional methods such as books to see its shape in 2D. The method used in the application of augmented reality in this study is markerless, so that the black and white square markers are replaced by pictorial markers presented in the Augmented Reality Book (AR Book) containing strawberries, lemons and cherries. From the results of alpha testing, the application made can function properly. From the results of the marker test, the application can display 3D objects at a marker distance of 5 cm - 60 cm, with a marker tilt angle of 30 ° - 60 ° and the marker is blocked by other objects up to 75%. From the results of the questionnaire calculation using the Likert's Sumated Rating (LSR) method, a score of 85 was obtained, so the assessment range was very positive, which means that the application can be implemented properly. And also the calculations carried out by the author in the evaluation of students showed that Ho was rejected because there was no significant effect on children's understanding, while H1 was accepted because of a significant influence on children's understanding.